In vitro degradation kinetics of pure PLA and Mg/PLA composite: Effects of immersion temperature and compression stress. (15th January 2017) - Li, Xuan; Chu, Chenglin; Wei, Yalin; Qi, Chenxi; Bai, Jing; Guo, Chao; Xue, Feng; Lin, Pinghua; Chu, Paul K.
Graphical abstract: Abstract: The effects of the immersion temperature and compression stress on the in vitro degradation behavior of pure poly-lactic acid (pure-PLA) and PLA-based composite unidirectionally reinforced with micro-arc oxidized magnesium alloy wires (Mg/PLA or MAO-MAWs/PLA) are investigated. The degradation kinetics of pure-PLA and the PLA matrix in MAO-MAWs/PLA exhibit an Arrhenius-type behavior. For the composite, the synergic degradation of MAO-MAWs maintains a steady pH and mitigates the degradation of PLA matrix during immersion. However, the external compression stress decreases the activation energy ( Ea ) and pre-exponential factor ( k0 ) consequently increasing the degradation rate of PLA. Under a compression stress of 1 MPa, Ea and k0 of pure PLA are 57.54 kJ/mol and 9.74 × 10 7  day −1, respectively, but 65.5 kJ/mol and 9.81 × 10 8  day −1 for the PLA matrix in the composite. Accelerated tests are conducted in rising immersion temperature in order to shorten the experimental time. Our analysis indicates there are well-defined relationships between the bending strength of the specimens and the PLA molecular weight during immersion, which are independent of the degradation temperature and external compression stress. Finally, a numerical model is established to elucidate the relationship of bending strength, the PLA molecular weight, activation energy, immersion time and temperature. Statement of significance: We systematically evaluate the effects of compression stress and temperature on the degradation properties of two materials: (pure-PLA) and MAO-MAWs/PLA (or Mg/PLA). The initial in vitro degradation kinetics of the unstressed or stressed pure-PLA and MAO-MAWs/PLA composite is confirmed to be Arrhenius-like. MAO-MAWs and external compression stress would influence the degradation activation energy ( Ea ) and pre-exponential factor ( k0 ) of PLA, and we noticed there is a linear relationship between Ea and ln k0 . Thereafter, we noticed that Mg 2+, not H +, plays a significant role on the mitigation of the PLA degradation and external compression stress brings the molecular structure change of PLA. Finally, we proposed a model to predict the bending strength of the specimens versus immersion time at different immersion temperatures. This fundamental study could provide some scientific basis in our understanding for the evaluations and biomedical applications of these biodegradable materials.